2016
DOI: 10.1039/c6ra11819d
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of highly crystalline, multifunctional iron oxide nanocomposites for imaging applications

Abstract: We report a single-step, microwave-assisted approach for the preparation of multifunctional magnetic nanocomposites. We demonstrate the link between synthetic methodology and the functionality of the nanocomposites as biomedical imaging agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 70 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…4). Williams et al (2016) have reported the synthesis of polymersupported multifunctional magnetite nanoparticles via microwave heating method at 150°C for 20 min. In a single step, aggregated nanoparticles with high crystallinity and aqueous stability were prepared using FeCl 3 .6H 2 O and FeCl 2 .4H 2 O as precursors.…”
Section: Microwave-assisted Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…4). Williams et al (2016) have reported the synthesis of polymersupported multifunctional magnetite nanoparticles via microwave heating method at 150°C for 20 min. In a single step, aggregated nanoparticles with high crystallinity and aqueous stability were prepared using FeCl 3 .6H 2 O and FeCl 2 .4H 2 O as precursors.…”
Section: Microwave-assisted Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Stoichiometric amounts of FeCl 3 ⋅ 6H 2 O (20 mmol), FeSO 4 ⋅ 7H 2 O (10 mmol) and 4.8 gm of urea (30 mmol) were dissolved in 50 mL DIW, then heated the reaction mixture in the microwave at 700 power and 160 °C for 1 h . The reaction mixture was cooled to room temperature and the formed precipitates were separated by centrifuge, washed with DIW and ethanol then dried it in an oven at 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…When two immiscible solvents are mixed together, a thermodynamically stable isotropic dispersion is formed which is defined as microemulsion with the presence of an interfacial layer of surfactant's molecules (de Toledo et al, 2018). Surfactants molecules generally bearing hydrophilic heads soluble in water and hydrophobic tails soluble in oil phase form a monolayer at the interface of the two immiscible liquids (wateroil) (Williams et al, 2016). Surfactant is an amphiphilic molecule playing a role to lower the water-oil interfacial tension to give a transparent solution.…”
Section: Microemulsion Synthesismentioning
confidence: 99%
“…A wide range of magnetic nanomaterials have been synthesized using the microemulsion method with good control and the sizes, as well as shapes, usually varied over a wider range. In the microemulsion technique, large quantities of solvents are used to produce considerable amounts of nanomaterial; based on this, it's categorized as a very efficient procedure and relatively difficult to be applied at large scale ( Figure 6) (Kumar et al, 2013;Williams et al, 2016).…”
Section: Microemulsion Synthesismentioning
confidence: 99%
See 1 more Smart Citation